Revitalization of Vacant Land for Sustainable Tourism Village Development: Study of KKNP 55 UMS in Padi Village: Revitalisasi Lahan Kosong untuk Pengembangan Desa Wisata Berkelanjutan: Studi KKNP 55 UMS di Desa Padi - Sabrina, Alfifah Faizatus; Ghaviansyah, Firdan Isya; Putry, Hanny Pradany; Aviana, Rizqillah Dita; Setiyawati, Enik (Journal of Empowerment and Community Service (JECSR), 2024)
The revitalization of vacant land around water bodies is one of the strategies for developing sustainable tourism villages. Padi Village, located in Gondang District, Mojokerto Regency, has significant potential to transform unproductive land into an eco-based tourist destination. The Kuliah Kerja Nyata Pencerahan (KKN-P) program of group 55 from Universitas Muhammadiyah Sidoarjo focuses on land revitalization by establishing Ecovibe Garden, an educational tourism park that prioritizes sustainability and environmental conservation. This study employs a qualitative descriptive approach using observation, interviews, and documentation to analyze the impact of revitalization on the community and the environment. The results indicate that this revitalization initiative enhances tourism appeal, creates new economic opportunities for the local community, and raises awareness about environmental conservation. Through collaboration between academics, the government, and the community, this program is expected to serve as a model for sustainable tourism village development.